ANALISIS STRATEGI INVESTASI BERBASIS DIVIDEND YIELD - THE FOOLISH FOUR PADA BURSA EFEK INDONESIA - , Galih Permadi Bahar ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The Foolish Four is one of the dividend yield-based portfolio strategy. This strategy became famous during 90âs until early 2000 because the return of the portfolio that successfully outperformed market index. Despite the controversy it created, studies in several market in several countries such as U.S., Canada, and South Africa had shown rate of return that consistently outperformed marketâs. By doing data simulation from 2003 until 2012 in Indonesia stock market, this study finds out how the strategy performs in local market with LQ45 index as the main benchmark. The nature of this strategy which only requires four stock on its portfolio can be an alternative investment guide for small investors considering the risk-adjusted return of each portfolio strategy.